2013
DOI: 10.1210/jc.2012-3791
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Medium-Chain Acyl–Coenzyme A Dehydrogenase Deficiency Have Impaired Oxidation of Fat During Exercise but No Effect ofl-Carnitine Supplementation

Abstract: Our results indicate that patients with MCADD have an impaired ability to increase FAO during exercise but less so than that observed in patients with a number of other disorders of fat oxidation, which explains the milder skeletal muscle phenotype in MCADD. The use of carnitine supplementation in MCADD cannot be supported by the present findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Imamura and colleagues created a genetic risk score model using 49 susceptibility alleles (GRS-49) for T2D in a Japanese population and discovered an increased level of AUC with combined GRS-49 and clinical factors (including age, sex, and BMI) compared with each individually. But the AUC value is only 0.773, which shows a clinically modest but statistically significant effect on T2D [141]. This phenomenon is also observed in many other studies from different ethnic groups [142, 143].…”
Section: Clinical Utility Of Genetic Information: Prediction Of Tymentioning
confidence: 57%
“…Imamura and colleagues created a genetic risk score model using 49 susceptibility alleles (GRS-49) for T2D in a Japanese population and discovered an increased level of AUC with combined GRS-49 and clinical factors (including age, sex, and BMI) compared with each individually. But the AUC value is only 0.773, which shows a clinically modest but statistically significant effect on T2D [141]. This phenomenon is also observed in many other studies from different ethnic groups [142, 143].…”
Section: Clinical Utility Of Genetic Information: Prediction Of Tymentioning
confidence: 57%
“…Reference mean levels in normal subjects were reported by Opalka et al (2001) and Madsen et al (2013) to be 2,400 (800) and 2,914 (249) nmol/g wet weight of muscle tissue, respectively. The difference in reported mean values by Opalka et al and Madsen et al might have been caused by an age difference between the cohorts -as mean muscle free carnitine levels reportedly decrease with age (Opalka et al 2001).…”
Section: Discussionmentioning
confidence: 74%
“…Data from other patient groups with secondary carnitine depletion (as opposed to those with PCD) are not conclusive concerning a beneficial effect of L-carnitine supplementation, e.g. as in MCADD (medium-chain acylCoA dehydrogenase deficiency) patients (Madsen et al 2013). Supplementation in patients with LCHADD (longchain 3-hydroxyacyl-CoA dehydrogenase deficiency) on the other hand may cause increased production of toxic 3-hydroxyacylcarnitines (Spiekerkoetter et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 ). As such, between group comparisons were made using an unpaired t-test as it has been previously demonstrated that the t-test is a valid approach and outperforms the non-parametric…”
Section: Discussionmentioning
confidence: 99%